Public Opinion on Education Policy in Germany - Philipp Lergetporer; Katharina Werner; Ludger Woessmann (Institute of Labor Economics (IZA), 2017)
To better understand the political economy constraints of education policy, we have conducted the annual ifo Education Survey in Germany since 2014. This paper summarizes selected key findings on the German publics' preferences for education policies ranging from early childhood education and schools to the apprenticeship system, universities, and lifelong learning. While the emerging picture is complex and multifaceted, some general patterns emerge. The majority of Germans is surprisingly open to education reform and favors clear performance orientation. Survey experiments indicate that information can have substantial effects on public policy preferences. Overall, education policies seem important for respondents' voting behavior.
Keywords: I28; D72; H52; 330; education policy; public opinion; political economy; survey experiments; Germany